1985
DOI: 10.1159/000115765
|View full text |Cite
|
Sign up to set email alerts
|

Preventive Treatment of Cerebral Transient Ischemia: Comparative Randomized Trial of Pentoxifylline versus Conventional Antiaggregants

Abstract: A comparative study of the prevention of recurrences of cerebral transient ischemic attacks during a 6-month observation period was conducted in 73 patients treated with a combination of acetylsalicylic acid and dipyridamole (ASAD, 1,050 mg + 150 mg/day) and in 65 patients treated with pentoxifylline (PTX 1,200 mg/day, Trental® 400 t.d.s). The patients were randomly assigned to the treatments. Risk factor analysis showed high prevalence of arterial hypertension, hyperlipidemia and smoking in these patients. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
3

Year Published

1987
1987
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(16 citation statements)
references
References 18 publications
1
12
0
3
Order By: Relevance
“…Pentoxifylline did not influence the elevated blood pressure in these rats, but histological examination of the brains of these rats showed that drug treatment prevented activation of microglia and influx of T-lymphocytes and macrophages. A 6-month randomised clinical trial enrolling patients experiencing transient ischaemic attacks (TIAs) assigned 73 patients to asprin+dipyridamole and 65 patients to pentoxifylline 47. During the trial, there were 80 TIAs in 19 patients in the aspirin/dipyridamole group, and 19 TIAs in 9 of those receiving pentoxifylline (p<0.05).…”
Section: Pentoxifylline: Myriad Potential Benefits For Vascular Healthmentioning
confidence: 99%
“…Pentoxifylline did not influence the elevated blood pressure in these rats, but histological examination of the brains of these rats showed that drug treatment prevented activation of microglia and influx of T-lymphocytes and macrophages. A 6-month randomised clinical trial enrolling patients experiencing transient ischaemic attacks (TIAs) assigned 73 patients to asprin+dipyridamole and 65 patients to pentoxifylline 47. During the trial, there were 80 TIAs in 19 patients in the aspirin/dipyridamole group, and 19 TIAs in 9 of those receiving pentoxifylline (p<0.05).…”
Section: Pentoxifylline: Myriad Potential Benefits For Vascular Healthmentioning
confidence: 99%
“…Additionally, pentox ifyllin decreased viscosity and leukocyte and platelet adhe sion to endothelial cell walls [99] and promoted PGT release from endothelial cells [100,101]. In human clinical studies, it appeared more effective than aspirin in stroke prevention [ 102], Most importantly, a group from Yugoslavia evaluated 51 ESRD patients [103] who underwent a Scribner shunt as an acute access while waiting for development of a permanent access. Twenty-six received pentoxifyllin (400 mg 3 times a day) and 25 placebo.…”
Section: Antiplatelet Agentsmentioning
confidence: 99%
“…26 Several clinical studies have suggested a potential therapeutic or prophylactic efficacy of PTX in ischemic cerebrovascular disorders. 27 " 32 Our study was designed to assess the efficacy and safety of PTX on the survival, neurologic deficits, and extent of recovery after acute nonhemorrhagic stroke using a randomized, placebocontrolled, double-blind protocol.…”
mentioning
confidence: 99%